Penerapan Mobilisasi Progresif Level I Terhadap Tekanan Darah Dan Saturasi Oksigen Pada Pasien Penurunan Kesadaran Di ICU RSUD dr. Soediran Mangun Sumarso Wonogiri - Fatin Nurhayati; Eska Dwi Prajayanti; Sumardi Sumardi (Lembaga Pengembangan Kinerja Dosen, 2023)
Background; Progressive Mobilization Level I can affect blood pressure and oxygen saturation in critically impaired patients with reduced consciousness. Progressive mobilization can affect oxygen saturation, this is because after being given level 1 progressive mobilization in the Head of Bed position, gravity will pull the diaphragm down resulting in better lung expansion (distributing oxygen in the lungs) so that the oxygen bound by hemoglobin increases. increase in oxygen saturation values. Objective; Knowing the results of applying level I progressive mobilization to blood pressure and oxygen saturation in patients with decreased consciousness. Method; The application was carried out using a case study descriptive method to 2 respondents in patients with decreased consciousness for 3 days with a frequency of 2 times a day for 15 minutes. Results; Based on the results of the application that has been carried out, there is a decrease in blood pressure and an increase in oxygen saturation before and after the application of level I progressive mobilization. Conclusion; Level I Progressive Mobilization can be used as a non-pharmacological technique or independent intervention in patients with decreased consciousness to reduce blood pressure and increase oxygen saturation.